ChemInform Abstract: Ligand‐Free Pd‐Catalyzed Domino Synthesis of Carbazoles via Dehydrogenative Aromatization/C(sp2)—C(sp2) Coupling Sequence. Issue 31 (14th July 2016) - Wen, Lixian; Tang, Lin; Yang, Yu; Zha, Zhenggen; Wang, Zhiyong
Abstract: The protocol works in the absence of a ligand and can be applied to a series of anilines and cyclohexanones.